Clinical study of outcome of operative management of locally advanced breast carcinoma after neoadjuvant chemotherapy at tertiary care hospital - Jivani, Sachin; Chovatiya, Nisarg; Patel, Kautilya; Zala, Jahnavi; Gupta, Rohan; Pancholi, Mukesh (International Surgery Journal, 2022)
Background: Locally advanced diseased of the breast is characterised clinically by features suggesting infiltration of the skin or chest wall by tumour or matted involved axillary nodes (AJCC-stage III). Successful reduction in the size of the tumor is associated with increased rate of operability i.e., modified radical mastectomy or breast conserving therapy (BCT). The aim of this study is to assess outcome of surgery in management of locally advanced breast carcinoma (LABC) after neoadjuvant chemotherapy. Methods: It is an observational retrospective study of 40 cases of LABC admitted at general surgery department. Results: The response to neoadjuvant chemotherapy was seen in 92.5% cases- with complete response in 10% cases (4 patients) and partial response in 82.5% (33 patients). No response was observed in 7.5% cases (3 patients) after 4 cycles of neoadjuvant chemotherapy. All patients were subjected to surgery after chemotherapy, out of whom 02 patients (5%) have surgical site infection and flap necrosis in 01 patient (2.5%) and no mortality; 02 patients subjected to toilet mastectomy without neoadjuvant chemotherapy resulted in 01 recurrence within 6 months of completion of adjuvant therapy and 01 death postoperatively. Conclusions: Majority of patients were subjected to neoadjuvant chemotherapy responded partially to it. Overall observations suggested that most of the LABC responds to neoadjuvant chemotherapy with minimum post-operative morbidity and mortality.